The role of communication strategies in the modelling of structure of knowledge-based society (Herald of Journalism, 2020)
The article discusses the role of humanitarian technologies in the de- velopment of intellectual society in Kazakhstan. The authors explore the integrative role of communication strategies in shaping spiritual and moral values of the society in Kazakhstan.
Keywords: intelligent nation, intelligence, humanitarian technology, communication strategies.